The effect of Status Quo (SQ) interpretation on welfare estimates: An application of white water rafting (WWR) - Hasan Basri, Bakti; Rawi, Shamsul Bahrain; Omar, Hamimi; Mohamad @ Alwi, Mohamad Khairi (2013)
Choice Experiment (CE) technique requires respondents to choose the most preferred alternative from a series of alternatives presented to them.One of these alternatives is Status Quo (SQ) option which resembles the current scenario.However, respondents’ interpretation of SQ may differ.This is inevitable for environmental goods.Using the case study of white water rafting (WWR) activity, this article investigates the effects of respondents’ willingness to pay (WTP) when they are allowed to define their own SQ.Three types of SQ are being investigated: a) individual interpretation; b) group interpretation; and c) authors’ interpretation.The results show that the personal and group interpret ations of SQ produce better results compared to the authors’ interpretation at least in significance of attributes.This indicates that in complex choice experiment exercises, the determination of the SQ should be decided by the respondents rather than by the researcher.